Exposure to perfluoroalkyl substances and thyroid function in pregnant women and children: A systematic review of epidemiologic studies. (February 2017) - Ballesteros, Virginia; Costa, Olga; Iñiguez, Carmen; Fletcher, Tony; Ballester, Ferran; Lopez-Espinosa, Maria-Jose
Abstract: Introduction: Thyroid hormones (THs) are especially important for brain maturation and development during the fetal period and childhood. Several epidemiological studies have assessed the possible association between exposure to perfluoroalkyl substances (PFAS) and thyroid outcomes during the early stages of life. We aimed to review this evidence. Methods: We conducted a systematic review in compliance with the PRISMA Statement (search conducted in PubMed and Embase, as well as in the citations of the selected articles). We chose studies if they dealt with thyroid-stimulating hormone (TSH), triiodothyronine (T3), thyroxin (T4), or thyroid dysfunctions, and perfluorohexane sulfonate (PFHxS), perfluorooctanoic acid (PFOA), perfluorooctane sulfonate (PFOS) or perfluorononanoic acid (PFNA) measured in the blood of pregnant women and/or children up to 19 years old. Results: We included in this review three cross-sectional, one case-control, and six cohort studies (publication: 2011–2015), focusing on prenatal life ( n  = 7), childhood ( n  = 2) or both periods ( n  = 1). We observed a high degree of heterogeneity across studies in terms of sampling time (different gestational weeks, at birth, or childhood), outcomes, adjustment for potential confounders, and statistical approach. We found some evidence of a positive association between PFHxS and PFOS exposure and TSH levels measured in maternal blood, and PFNA and TSH levels measured in the blood of boys aged ≥ 11 years. Conclusion: Although there is a small number of studies with comparable data, we found some consistency of a positive association between maternal or teenage male exposure to some PFAS and TSH levels based on the current literature. However, further studies are required to confirm these possible relationships. Highlights: First review on PFAS exposure and thyroid outcomes during pregnancy and childhood Scarce comparable studies due to great heterogeneity across them Some evidence of a positive association between maternal PFHxS and PFOS exposure and TSH levels Some evidence of a positive association between TSH and PFNA levels in boys ≥ 11 years No evidence of other thyroid dysfunction or hormones related to PFAS